2023
DOI: 10.1051/0004-6361/202245235
|View full text |Cite
|
Sign up to set email alerts
|

The SOUL view of IRAS 20126+4104

Abstract: Context. We exploit the increased sensitivity of the recently installed adaptive optics SOUL at the LBT to obtain new high-spatial-resolution near-infrared images of the massive young stellar object IRAS20126+4104 and its outflow. Aims. We aim to derive the jet proper motions and kinematics, as well as to study its photometric variability by combining the novel performances of SOUL together with previous near-infrared images. Methods. We used both broad-band (Ks, K′) and narrow-band (Brγ, H2) observations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…This velocity is consistent with previously measured jet knots ejected by massive protostars (e.g. Fedriani et al 2019;Massi et al 2023). This interpretation is supported by the fact that the other jet tracers in the radio regime align with the NIR NE knot.…”
Section: Episodic Ejection As a Response To Episodic Accretionsupporting
confidence: 91%
See 1 more Smart Citation
“…This velocity is consistent with previously measured jet knots ejected by massive protostars (e.g. Fedriani et al 2019;Massi et al 2023). This interpretation is supported by the fact that the other jet tracers in the radio regime align with the NIR NE knot.…”
Section: Episodic Ejection As a Response To Episodic Accretionsupporting
confidence: 91%
“…From our AO imaging data, we can estimate the ejection time scale of these H 2 knots. It has been observed that H 2 knots driven by HMYSOs can have velocities exceeding 100 km s −1 (see, e.g., Fedriani et al 2018;Massi et al 2023). This would imply that the dynamic age of the NIRS3 H 2 knots is ∼ 400 − 700 years.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, n H 2 < 5 × 10 4 cm −3 , as shown in Fig. 13, and sh < ∼ 100 km s −1 , which was obtained from proper motion measurements of the H 2 O masers (Moscadelli et al 2005(Moscadelli et al , 2011 and H 2 knots (Massi et al 2023). Therefore, n H 2 sh < 5 × 10 11 cm −2 s −1 , which satisfies the previous condition.…”
Section: Shocked Regionsupporting
confidence: 81%
“…The (proto)star is powering a outflow undergoing precession about the disk axis (Shepherd et al 2000;Cesaroni et al 2005;Caratti o Garatti et al 2008). This outflow has been imaged on scales from a few 100 au (Moscadelli et al 2005;Cesaroni et al 2013) to 0.5 pc (Shepherd et al 2000;Lebrón et al 2006) and its 3D expansion velocity has been measured through maser and H 2 -knot proper motions (Moscadelli et al 2005;Massi et al 2023). The distance to IRAS 20126+4104 (1.64±0.05 kpc) has been accurately determined from parallax measurements of the H 2 O masers (Moscadelli et al 2011), which prove this to be one of the closest disks around B-type (proto)stars, thus allowing for excellent linear resolution.…”
Section: Introductionmentioning
confidence: 99%
“…These two types of models can be applied to the jet and knot positions, directly relating periodicity in the knot positions to the binary period or precession period (e.g., Raga et al 2002). Most prior work focuses on molecular jets with small wiggles and opening angles (i.e., the angular width of the jet) of <10°; these are usually interpreted in terms of binary motion (Gueth et al 1996;Zinnecker et al 1998;Woitas et al 2002;Chandler et al 2005;Sahai et al 2005;Ybarra et al 2006;Seale & Looney 2008;Phillips & Pérez-Grana 2009;Lee et al 2010Lee et al , 2015Whelan et al 2010;Agra-Amboage et al 2011;Noriega-Crespo et al 2011, 2020Estalella et al 2012;Fernández-López et al 2013;Velázquez et al 2014;Kwon et al 2015;Beltrán et al 2016;Moraghan et al 2016;Choi et al 2017;Louvet et al 2018;Hara et al 2021;Jhan & Lee 2021;Murphy et al 2021;Massi et al 2022Massi et al , 2023.…”
Section: Introductionmentioning
confidence: 99%